2013
DOI: 10.1016/j.atherosclerosis.2012.12.012
|View full text |Cite|
|
Sign up to set email alerts
|

Adiponectin inhibits macrophage tissue factor, a key trigger of thrombosis in disrupted atherosclerotic plaques

Abstract: Objective Adiponectin (APN) is an adipocytokine with anti-atherogenic and anti-inflammatory properties. Hypoadiponectinemia may associate with increased risk for coronary artery disease (CAD) and acute coronary syndrome (ACS). Tissue factor (TF) initiates thrombus formation and facilitates luminal occlusion after plaque rupture, a common cause of fatal ACS. This study tested the hypothesis that APN influences TF expression by macrophages (MΦ), inflammatory cells found in atheromatous plaques. Methods Human m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
0
13
1
2
Order By: Relevance
“…Therefore, chemerin may be involved in different stages of atherosclerosis through regulating the migration of macrophage. In contrary, accumulating evidence demonstrated that adiponectin not only suppresses foam cell transformation but also inhibits the pro-coagulant activity of macrophage [37]. In the present study, a high level of chemrin and a low level of adiponectin were detected in ACS, suggesting the imbalance of pro-inflammatory/anti-inflammatory adipokines may be associated with the presence of ACS by regulation the activity of macrophage.…”
Section: Discussioncontrasting
confidence: 79%
“…Therefore, chemerin may be involved in different stages of atherosclerosis through regulating the migration of macrophage. In contrary, accumulating evidence demonstrated that adiponectin not only suppresses foam cell transformation but also inhibits the pro-coagulant activity of macrophage [37]. In the present study, a high level of chemrin and a low level of adiponectin were detected in ACS, suggesting the imbalance of pro-inflammatory/anti-inflammatory adipokines may be associated with the presence of ACS by regulation the activity of macrophage.…”
Section: Discussioncontrasting
confidence: 79%
“…Evidence derived from the in vitro study suggested that APN was able to inhibit the macrophage tissue factor, a key molecule promoting thrombus formation in disrupted plaques [29]. In APN-knockout mice, APN deficiency was associated with enhanced thrombus formation and platelet aggregation [11].…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin, one of the most abundant adipokines, is capable of reducing leukocyte–endothelial interactions [48,49] and inhibiting smooth muscle cell proliferation [50]. Adiponectin also stimulates nitric oxide production in endothelial cells, induces the synthesis of the anti-inflammatory cytokine IL-10 in macrophages [51], and inhibits tissue factor expression in both endothelial cells and macrophages [52,53 ▪ ]. Unfortunately, plasma levels of adiponectin tend to decrease as obesity progresses [30].…”
Section: Modulators Of Thrombotic Pathways In Obesitymentioning
confidence: 99%